The renin-angiotensin receptor blocker azilsartan medoxomil compared with the angiotensin-converting enzyme inhibitor ramipril in clinical trials versus routine practice: insights from the prospective EARLY registry. Issue 1 (December 2015) - Bramlage, Peter; Schmieder, Roland; Gitt, Anselm; Baumgart, Peter; Mahfoud, Felix; Buhck, Hartmut; Ouarrak, Taoufik; Ehmen, Martina; Potthoff, Sebastian
Abstract Background Patient characteristics and blood pressure-related outcomes in randomized clinical trials (RCTs) differ from clinical practice because of stringent selection criteria. The present study aimed to explore the relationship between clinical trials and clinical practice. We analyzed data from patients enrolled in the "Treatment with Azilsartan Compared to ACE-Inhibitors in Anti-Hypertensive Therapy" (EARLY) registry comparing blood pressure (BP) effects of the angiotensin receptor blocker (ARB) azilsartan medoxomil (AZL-M) with the angiotensin-converting enzyme (ACE) inhibitor ramipril between patients who met the eligibility criteria of a previous RCT and those who did not. Methods Patients with primary arterial hypertension were consecutively enrolled from primary care offices in Germany into the EARLY registry in a 7:3 ratio for treatment with AZL-M or an ACE inhibitor, provided that they met the following criteria at baseline: 1) no antihypertensive treatment prior to inclusion or a non-renin-angiotensin system (RAS) based monotherapy; 2) initiation of treatment with either AZL-M or an ACE inhibitor alone. Analyses were performed to evaluate BP effects for patients in the EARLY registry who met the selection criteria of a prior RCT (RCT+) versus those who did not (RCT-). Results Out of 3, 698 patients considered, 1, 644 complied with the RCT criteria (RCT+) while 2, 054 did not (RCT-). RCT- patients (55.5 %) displayed a higher risk profile in terms of age and comorbidities, and a wider spectrum of BP values at baseline, as highlighted by the grades of hypertension and mean BP values. The proportion of patients who achieved target blood pressure control in the RCT+ group was significantly higher for AZL-M versus ramipril (64.1 versus 56.1 %;P  < 0.01), in accordance with the result of the clinical trial. In the RCT- AZL-M group, the proportion of patients who met BP targets was lower (58.1 %) than in the RCT+ AZL-M group (64.1 %), whereas the proportion of patients with target BP values in the RCT- ramipril and the RCT+ ramipril groups was similar (57.7 versus 56.1 %). Thus, in contrast to results for the RCT+ group, in the RCT- group, the target BP attainment rate for AZL-M was not significantly superior to that for ramipril. However, the tolerability profile of AZL-M and ramipril was comparable in both populations. At the 12-month follow-up, death and stroke rates were low (≤0.5 %) and adverse events did not differ between the AZL-M and ramipril groups, irrespective of RCT eligibility. Conclusions These data confirm that the EARLY population comprised a broader spectrum of hypertensive patients than RCTs, and the differences in patient characteristics were accompanied by disparate rates of blood pressure goal attainment. Overall, the validity of the RCT was demonstrated and confirmed in clinical practice with a broader range of patients with various comorbidities.